Transaction Management in Homogenous Distributed Real-Time Grid Database Systems - Ratawa, Surya Prakash (IJRDO -Journal of Computer Science Engineering, 2017)
Distributed processing systems incorporating fully replicated databases are inherently more reliable than systems having partitioned and partially replicated databases. Since every site has a complete copy of the database, greater system functional integrity is provided in the event of network partitions. A network partition can occur when a break occurs in the communication medium isolating one or more processor sites. In addition to the greater reliability, there is a reduction in the associated control required. There is no need for the complicated mechanisms for maintaining owners (the primary data copy) and an acceptable number of subscriber copies (secondary copies or replications) of each database partition. There is also an improvement in performance obtainable from the use of local copies of data at each site. Faster access memory systems and higher speed communications improve performance of both partially and fully replicated database systems. However, potential improvements in performance can only be achieved by using update algorithms which require significantly less inter-site communication. An example of a homogeneous distributed processing system architecture incorporating a fully replicated database system. A homogenous distributed real time replicated database system is a network of two or more DBMS that reside on one or more machines. A distributed system that connects two or more databases are Homogenous Distributed Database Systems (HDDBS) create different problems when accessing distributed and replicated databases. Particularly, access control and transaction management in HDDBS require different mechanism to monitor data retrieval and update to databases. Current trends in multi-tier client/server networks make DDBS an appropriated solution to provide access to and control over localized databases. This paper highlights the basic concepts underlying distributed database system including transaction management in in HDRTDBS.